1999
DOI: 10.1101/gad.13.13.1647
|View full text |Cite
|
Sign up to set email alerts
|

NeuroD is required for differentiation of the granule cells in the cerebellum and hippocampus

Abstract: NeuroD, a bHLH transcription factor, is implicated in differentiation of neurons and pancreatic ␤ cells. NeuroD-null mice die shortly after birth due to severe neonatal diabetes. To examine if there is postnatal neuronal phenotype in these mice, we rescued them from neonatal lethality by introducing a transgene encoding the mouse neuroD gene under the insulin promoter. These mice survive to adulthood but display severe neurological phenotype due to neuronal deficit in the granule layers of the cerebellum and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
457
2
6

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 503 publications
(492 citation statements)
references
References 23 publications
17
457
2
6
Order By: Relevance
“…Similar to the results of previous reports in Bax single null mice (Knudson et al, 1995), ND +/-Bax +/-and ND +/-Bax -/-did not generate any ectopic phenotype except male infertility. Most of the ND -/-Bax +/+ , ND -/-Bax +/-and ND -/-Bax -/-mice died within 3 days postpartum, suggesting that the disruption of Bax did not rescue the pancreatic cell death and resulting severe diabetes caused by the mutation of NeuroD (Miyata et al, 1999;Naya et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar to the results of previous reports in Bax single null mice (Knudson et al, 1995), ND +/-Bax +/-and ND +/-Bax -/-did not generate any ectopic phenotype except male infertility. Most of the ND -/-Bax +/+ , ND -/-Bax +/-and ND -/-Bax -/-mice died within 3 days postpartum, suggesting that the disruption of Bax did not rescue the pancreatic cell death and resulting severe diabetes caused by the mutation of NeuroD (Miyata et al, 1999;Naya et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…The Bcl-2 family protein Bax is required for neuronal death upon neurotrophin deprivation (Deckwerth et al, 1996). It has been suggested that the cell death of NeuroD null cerebellum, hippocampus and inner ear cells was mediated by apoptosis (Kim et al, 2001;Miyata et al, 1999). In the present study, it was examined whether the elimination of the Bax protein rescues cells from cell death.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Ngn1 or Ngn2 single knockout mice showed complementary loss of cranial sensory ganglia, whereas the Ngn1/2 double knockout mice lacked the spinal sensory ganglia as well as a majority of ventral spinal cord neurons, due to, as for Mash1, an early defect in neurogenesis [40,45,46]. NeuroD1 null mice have defects in the granule layers of the cerebellum and hippocampus, and in the inner ear sensory neurons because of a later function of NeuroD1 in neuronal differentiation [47,48]. Understanding the mechanism of how different neural bHLH factors integrate positional information into the process of neurogenesis will facilitate the generation of multiple types of neural cells from pluripotent stem cells in vitro.…”
Section: Discussionmentioning
confidence: 99%